Negotiating multicultural values within centralized education systems: a case study of Indonesia - Afifuddin, Afifuddin; Amri, Muhammad; Latif, Abdul; Rosmini, Rosmini; Bin Tahir, Saidna Zulfiqar (Frontiers in Education, 2025)
As in many education systems worldwide, Indonesian society is increasingly characterized by cultural diversity. In the context of centralized education policies, multicultural issues have become more visible in primary schools. This study aimed to explore the attitudes and classroom practices of elementary school teachers in Indonesia regarding multicultural education. A mixed-methods approach utilizing a concurrent triangulation design was employed. Data were collected through a multicultural education attitude survey and semi-structured interviews. In the quantitative phase, a multiculturalism attitude scale was administered to 30 randomly selected primary school teachers. The survey results indicated moderately positive attitudes toward multicultural values, with minor variations based on age and teaching experience. In the qualitative phase, interviews and classroom observations were conducted with 10 teachers. The findings revealed that while teachers recognized multiculturalism mainly through ethnicity, religion, and language differences, they perceived substantial gaps between policy expectations and classroom realities. Teachers noted a lack of institutional support and limited curriculum flexibility as major barriers to implementing multicultural education. Many expressed that their understanding of multicultural pedagogy was incomplete and showed interest in participating in professional development programs to enhance their competence. The study highlights the critical need for more responsive policies and teacher training initiatives to bridge the gap between centralized standards and multicultural classroom dynamics.